(untitled) (RuMoRes, 2013)
This work focus on the subject's image built through photography as the base of "reality" in virtual space. We seek to understand which significances and uses emerged from manipulation/appropriation of the photography act in the composition of the user's profile in social networking sites. In order to discuss these premises, a participant observation was carried, followed by the application of 217 surveys (with open questions) in social network sites (such as Orkut, Facebook, Plurk, Twitter e Flickr). We observed that users create different significances for the use of photography, which not only involve the subjects' identification in the system (connected to the "reality" notion), but the search for creating a self image as well, in order to aggregate social values.